2014
DOI: 10.5897/jdae2013.0525
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of technical efficiency and its determinants in beef cattle production in Kenya

Abstract: The stochastic metafrontier method is applied to estimate technical efficiency levels in beef cattle production in Kenya. Subsequently, a Tobit model is used to assess factors that might influence efficiency. Results show that the average efficiency level is 0.69, suggesting that there is considerable scope to improve beef production in Kenya. Considering the importance of the livestock enterprise to rural livelihoods and its potential role in poverty reduction, there is need for appropriate development strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The technical efficiency of beef cattle farms in Kenya demonstrated the same range as Malaysia's beef cattle farms where they had an average technical efficiency level of 0.69. Regardless of their production system, the farms had been analysed to be using an available technology sub optimally (David et al, 2014). Meanwhile, the three type of rearing system in Nigeria have their score of 0.59, 0.69 and 0.83 for the nomadic pastoralists, agropastoralists and ranchers system (Nwigwe et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technical efficiency of beef cattle farms in Kenya demonstrated the same range as Malaysia's beef cattle farms where they had an average technical efficiency level of 0.69. Regardless of their production system, the farms had been analysed to be using an available technology sub optimally (David et al, 2014). Meanwhile, the three type of rearing system in Nigeria have their score of 0.59, 0.69 and 0.83 for the nomadic pastoralists, agropastoralists and ranchers system (Nwigwe et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many case studies (e.g. Alvarez-del Corral [2010], Sauer-Davidova-Gorton [2012], Kellermann [2014], Otieno Hubbard-Ruto [2014, Baráth-Fertő [2013], Martinez et al [2016], Bahta et al [2018]) have shown resource and production environments surrounding production societies are highly heterogeneous. The use of a single characteristic to cluster a sample might be challenging when heterogeneity is likely to arise from more than one factor, leading to incomplete division of the sample.…”
Section: Model Specificationmentioning
confidence: 99%
“…), and second stage estimation of separated frontier functions for each group (e.g. Battese-Rao-O'Donnell [2004], Newman-Matthews [2006], Balcombe-Rahman-Smith [2007], Moreira-Bravo-Ureta [2010], Otieno-Hubbard-Ruto [2014], Melo-Becerra-Orozco-Gallo [2017]). 7 However, the use of a priori information might be challenging in cases where heterogeneity is likely to arise from more than one factor, leading to incomplete division of the sample (Alvarezdel Corral-Tauer [2012], Sauer-Morrison Paul [2013]).…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation